The effects of two different fatigue protocols on movement quality during anticipated and unanticipated change of directions in female soccer players - Alimoradi, M.; Hosseini, E.; Sahebozamani, M.; Dos`Santos, T.; Sheikhbahaie, S.; Bigtashkhani, R.; Kabiri, A. (PLOS ONE, 2024)
Objective This study compared neuromuscular control under two fatigue protocols during anticipated and unanticipated change of direction (COD) maneuvers and evaluated their effects on the risk of non-contact ACL injuries.